Spiritual distress, hopelessness, and depression in palliative care: simultaneous concept analysis - Martins, Helga (2024)
Spiritual distress, hopelessness, and depression are concepts that are often used in palliative care. A simultaneous concept analysis (SCA) of these concepts is needed to clarify the terminology used in palliative care. Therefore, the aim of this study is to conduct a SCA of spiritual distress, hopelessness, and depression in palliative care. A SCA was performed using the methodology of Haase’s model. A literature search was conducted in March 2020 and updated in April 2022 and April 2024. The search was performed on the following online databases: CINAHL with Full-Text, MEDLINE with Full-Text, MedicLatina, LILACS, SciELO, and PubMed. The search was achieved without restrictions on the date of publication. A total of 84 articles were included in this study. The results highlight that the three concepts are different but also share some overlapping points. Spiritual distress is embedded in the rupture of their spiritual/religious belief systems, a lack of meaning in life, and existential issues. Hopelessness is a sense of giving up and an inability to control and fix the patient’s situation. Finally, depression is a state of sadness with a multi-impaired situation. In conclusion, refining the three concepts in palliative care is essential since it promotes clarification and enhances knowledge development towards intervention.